TINJAUAN ASAS KEBEBASAN DALAM PERJANJIAN SEWA-MENYEWA MENURUT HUKUM PERDATA DAN HUKUM ISLAM - Wahyu Try Widodo (Universitas 17 Agustus 1945 Samarinda, 2014)
ABSTACK Rent - rent as well as purchase and sale agreements - agreements in general, it is valid and binding on the second achievement of agreed obligations of the parties submit the goods to be enjoyed by others, while the other party liabilities, paying rents. So the goods were handed over to law owned but only to be used, enjoyed its usefulness. Thus the mere transfer of power on the leased item. If an item assigned to wear, without the obligation to pay, then there is the mere agreement. If the user of goods is required to pay, mentioned tenancy. As followers of Islam believe that Islamic law as a law that has some of the rules in the law itself was also providing advice and guidance to obtain the true mandate of the development potential of goodness in human beings in everyday life, both in relation to cultural issues and problems muamalah, but it is still less attention to discuss separately.